EFFECT OF MDMV ON CORN GRAIN QUALITY - Собирова З. Ш.; Файзиев В. Б. (Journals Park Publishing, 2023)
Corn is one of the most widespread cereal crops in the world. Unfortunately, like many other plants, corn is susceptible to various diseases that are often found on the territory of Uzbekistan . Among pests, corn borers, swedish flies, aphids and cutworms cause great harm to corn. They cause significant damage to crops, the total yield can be reduced by 30-35%. About 3000 phytoviruses are known in the world. By the beginning of the 21st century, 1000 viruses have been described , of which more than 200 species of viruses that infect cereals have been identified, which are assigned to the families Bromoviridae, Potyviridae, Rhabdoviridae, Luteviridae [1]. Of these viruses, the most common is the dwarf mosaic virus. Maize dwarf mosaic potyvirus ( MDMV ) causes a characteristic mosaic lesion of leaf blades.